ANALISIS HAMBATAN DAN POTENSI SERTA STRATEGI PEMBERDAYAAN USAHA KECIL DALAM MENGHADAPI TANTANGAN GLOBAL ASEAN - Panjaitan Herman (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT Fragility of Indonesia's economic fundamentals prompted the government to build the economic structure taking into account the existence of Micro, Small and Medium Enterprises. This sector has proven to provide substantial employment and provides opportunities for develop in society. MSME's existence can not be doubted because it proved able to survive and become a engine of economy, especially after the economic crisis. On the other hand, also face many problems, namely limited working capital, human resources are low, and less cakapnya mastery of science and technology  Another obstacle faced the links with business prospects are less clear and the planning vision and mission that has not been steady. Provision of market information and networks, ease of access to funding and capacity building assistance and information technology are a strategy to improve the competitiveness in Indonesia. It is therefore necessary synergy between all parties, especially the government and microfinance institutions.